2005
DOI: 10.1063/1.1941367
|View full text |Cite
|
Sign up to set email alerts
|

Secondary instability in forced wavelength Görtler vortices

Abstract: From an experimental study on the onset of secondary instability in forced wavelength Görtler vortices, it is found that the breakdown process of the Görtler vortices is due to the development of varicose and sinuous mode instabilities. The development of the varicose mode is characterized by the formation of horseshoe vortices that evolve downstream to form mushroom-like structures. This phenomenon is then followed by meandering of the vortices as an indication of the onset of sinuous mode instability, prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…This agrees with Schmid and Henningson (2001) who found that once the disturbance has reached a finite amplitude at which the boundary-layer flow is dominated by the mushroom-like structures, it often saturates and transforms the flow into a new possibly steady state in which secondary instabilities can grow. However, the spectrum analysis of the fluctuating component u′ shows that the secondary instabilities arise prior to the non-linear saturation as exhibited by the formation of the peak in the spectrum with a band between 50 to 200 Hz at the streamwise location, where the amplitude of the disturbance is still developing (Mitsudharmadi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with Schmid and Henningson (2001) who found that once the disturbance has reached a finite amplitude at which the boundary-layer flow is dominated by the mushroom-like structures, it often saturates and transforms the flow into a new possibly steady state in which secondary instabilities can grow. However, the spectrum analysis of the fluctuating component u′ shows that the secondary instabilities arise prior to the non-linear saturation as exhibited by the formation of the peak in the spectrum with a band between 50 to 200 Hz at the streamwise location, where the amplitude of the disturbance is still developing (Mitsudharmadi et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The three global spanwise wavenumbers cover the (quasi-) most amplified Görtler modes in all the five Mach numbers. In the incompressible case, these wavenumbers coincide with the wavelengths 36, 18 and 9 mm considered in Li & Malik (1995 Swearingen & Blackwelder (1987) and Mitsudharmadi, Winoto & Shah (2005), K = −0.94 × 10 −6 and −2.5 × 10 −6 , respectively. The flow parameters of all the cases are listed in table 1.…”
Section: Spatial Development Of Görtler Vorticesmentioning
confidence: 86%
“…2͒ and apparatus used have been described in the previous work of Mitsudharmadi et al 3,16 However, a brief description of the experiment with the spanwise wire spacings of 7.5 and 30.0 mm will be given in the following. Six and thirteen vertical wires of 0.2 mm diameter are positioned at an upstream distance of 10.0 mm from the concave surface leading edge to provide wire spacing of 30.0 and 7.5 mm, respectively.…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…Liu and Domaradzki 13 also found that sinuous waves were observed first, and varicose mode in the form of hairpin vortices appeared later downstream. However, the experimental studies of Bakchinov et al, 14 Swearingen and Blackwelder, 9 Matsson,15 and Mitsudharmadi et al 16 show that a development of fluctuations on the spanwise structure coincide with the region of high shear at the mushroom-like structures to imply that the secondary instability is of varicose type at the onset.…”
Section: Introductionmentioning
confidence: 96%